Expression of adhesion molecules on leukocytes of patients with chronic venous insufficiency - Sˇtvrtinová, V.; Jahnová, E.; Labasˇ, P.; Weissová, S.; Horváthová, M.; Ferencík, M. (Phlebologie, 2002)
Aim: We studied if the expression and release of adhesion molecules is changed in peripheral lymphocytes obtained from patients with chronic venous insufficiency (CVI) of the lower limbs. Methods: 26 patients with CVI (19 primary varicose veins, 7 ulcus cruris) and 39 clinically healthy persons were included in our study. The expression of adhesion molecules on granulocytes, monocytes, and lymphocytes was analysed by flow cytometry. In serum soluble sCD31 and sCD54 was assayed by ELISA, the CD profile was estimated on lymphocytes. Results: In patients suffering from CVI the increased expression of CD11b, CD18, CD54, and CD49d on granulocytes and lymphocytes, of CD62L and CD49d on granulocytes and monocytes, and of CD15 on monocytes and lymphocytes was demonstrated. The highest difference in the expression of adhesion molecules between patients and controls were found on lymphocytes. In patients with CVI lower mean counts of cytotoxic (CD8+) lymphocytes and higher counts of NK cells (CD16+ + CD56+) were seen. The concentration of activated T lymphocytes (CD3 HLA-DR+) and of sCD54 was much higher in the circulation of patients with ulcus cruris than in those with varicose veins or in the controls. Conclusion: Lymphocytes and leukocytes of patients with CVI express elevated concentrations of various adhesion molecules, especially in patients with ulcus cruris. Additionally, significant changes in their CD profile were observed.
Keywords: Adhäsionsmoleküle; Lymphozyten; chronisch-venöse Insuffizienz